Manajemen Pembiayaan ANBK (Asesmen Nasional Berbasis Komputer) di Sekolah Dasar Kota Tasikmalaya - Karinta Utami; Ema Astri Muliasari; Cicin Solihati Fitria Firizqi; Nuryanti Surastri; Risbon Sianturi; Lutfi Nur (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The implementation of the National Assessment (AN) at the elementary school (SD) level in Indonesia is the first to be implemented in 2021. This is a challenge for every educational unit, especially regarding the financial aspect of the implementation of AN. The school unit implements AN, the first is to organize independently, and the second is to ride or share resources. In this research, we will take a case study of one school that organizes AN independently and one school that chooses the boarding method. The results of the study show two challenges that must be faced by education units, namely the AN budget that has not been included in the School Activity Plan and Budget (RKAS) at the beginning of the year and the unavailability of infrastructure facilities for the implementation of AN. The research shows an overview of the implementation of AN in the two different methods seen from the aspect of financing, so that it can be a lesson for the preparation of financing management for the implementation of AN SD in the Future.